Electronically Tunable VDCC-Based Floating Capacitance Multiplier - Kartci, Aslihan; Ayten, Umut Engin; Sotner, Roman; Arslanalp, Remzi (IEEE, 2015)
In this paper a new grounded capacitance multiplier using two Voltage Differencing Current Conveyors (VDCCs), two resistors, and one grounded capacitor is presented. The proposed capacitance multiplier can be tuned electronically by changing the biasing current of the VDCC. Moreover, the circuit does not require any conditions of component matching. The performance of the proposed capacitance multiplier is verified, and simulated by using PSPICE with TSMC CMOS 0.18 mu m process parameters.
Keywords: Capacitance multiplier; voltage differencing current conveyor; VDCC; electronically tuned; CMOS integrated circuits; Engineering; Telecommunications